1996
DOI: 10.1159/000171582
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hepatic Encephalopathy in Patients with Cirrhosis of the Liver

Abstract: The treatment of hepatic encephalopathy is predominantly an empirical approach because the process pathogenesis of this syndrome is uncertain. Many treatment trials have been published, but few fullfil the usually accepted criteria for optimum study design. Lack of placebo controls, inadequate sample size and the difficulty in assessing the severity of encephalopathy are noteworthy examples. Treatments based on reducing ammoniagenic factors in the intestinal tract and promoting urinary waste nitrogen eliminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Hepatic encephalopathy (HE) is a frequent and devastating complication of end‐stage liver disease. It is defined as a reversible brain dysfunction which manifests with a wide spectrum of neuropsychiatric abnormalities caused by liver insufficiency and portosystemic shunting . Clinically, it includes neurological and psychiatric abnormalities ranging from subclinical alterations to coma.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic encephalopathy (HE) is a frequent and devastating complication of end‐stage liver disease. It is defined as a reversible brain dysfunction which manifests with a wide spectrum of neuropsychiatric abnormalities caused by liver insufficiency and portosystemic shunting . Clinically, it includes neurological and psychiatric abnormalities ranging from subclinical alterations to coma.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the glutamine content of the enteral foods was increased by about 3.5% of the total amino acids. Branched chain amino acids (BCAA) are the major skeletal muscle proteins, which help localized metabolism besides improving the liver function (Ferrando et al, 1995;Ferenci, 1996). In addition, recently, Kakazu et al (2007) have reported the immune-enhancing effect of BCAA in cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in severely hypercatabolic conditions BCAA are utilized as a source of locally available energy in the skeletal muscle. The formulae enriched with BCAA help normalize the amino acid profile, improve protein synthesis, and maintain nitrogen balance (Ferenci, 1996). These products are often recommended for patients under major metabolic stress (Cerra et al, 1983;Mobarhan et al, 1990;Ferando et al, 1995).…”
Section: Disease-specific Formulaementioning
confidence: 99%
See 1 more Smart Citation
“…Although she comprehended questions and was oriented to situation, time, and place, she was lethargic and was a grade 2 per the West Haven Criteria for hepatic encephalopathy. 5 The patient weighed 51 kg, and her height was 150 cm (body mass index = 22.7 kg/m 2 ). Initial laboratory tests showed white blood count 20,000/µL, hematocrit 41%, platelets 141,000/µL, international normalized ratio 4.1, fibrinogen 50 mg/dL, a 2+ proteinuria, elevated creatinine 2.1 mg/dL, hypoglycemia 48 mg/dL, direct bilirubinemia 9.0 mg/dL, aspartate aminotransferase/alanine aminotransferase 59/63 U/L, alkaline phosphatase 1000 IU/L, and ammonia 101 mg/dL.…”
Section: Case Reportmentioning
confidence: 99%